Perlindungan Hukum Bagi Investor di Sektor Pariwisata - Renisitoresmi, Lovienna; Widiyanti, Ikarini Dwi; Kumala sari, Nuzulia (Lentera Hukum, 2016)
Indonesia is a country that has a variety of cultures and traditions in each region. In these cultural variations, each region will strive to create an object of tourism. With a large tourism object then it can be a contributor to foreign exchange for the Indonesian economy. Tourism is a prospective sector with a relatively large increase in investment realization. This increase is supported by the government's plan to enact Presidential Regulation number 39 of 2014 on closed business field and business field open to investment as supporting Law Number 25 the Year 2007 regarding Investment. The existence of sectors that support natural resources in Indonesia that can be utilized in the tourism sector, so this is where there are domestic and foreign investors who want to build more modern tourist objects. Indonesia needs to create a conducive investment climate, promotive, providing legal certainty, justice, and efficiency while maintaining national economic interests. KEYWORDS: Tourism Sector, Indonesian Culture, Investor, Legal Certainty, Legal Protection.